2001
DOI: 10.1063/1.1362335
|View full text |Cite
|
Sign up to set email alerts
|

Conduction band offset and electron effective mass in GaInNAs/GaAs quantum-well structures with low nitrogen concentration

Abstract: We have investigated the optical transitions in Ga1−yInyNxAs1−x/GaAs single and multiple quantum wells using photovoltaic measurements at room temperature. From a theoretical fit to the experimental data, the conduction band offset Qc, electron effective mass me*, and band gap energy Eg were estimated. It was found that the Qc is dependent on the indium concentration, but independent on the nitrogen concentration over the range x=(0–1)%. The me* of GaInNAs is much greater than that of InGaAs with the same conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 19 publications
8
53
1
1
Order By: Relevance
“…Therefore, the difference of the post-annealing effect on the PL properties between GaAsSbN and Ga(In)NAs systems might be related with the structure change of material. For GaNAs system, the N atoms reorganization assisted by the point-defect during annealing process is the main reason for blueshift [19,22,23]. The larger blueshift appeared in GaInNAs system than in GaNAs system is due to the additional effect induced by the existent of In atoms in annealing process, such as the In-N interaction or the formation of N-In bonds due to the Ga site around N atom replaced by In atom through the point-defect assisted reorganization in the annealing process [24].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the difference of the post-annealing effect on the PL properties between GaAsSbN and Ga(In)NAs systems might be related with the structure change of material. For GaNAs system, the N atoms reorganization assisted by the point-defect during annealing process is the main reason for blueshift [19,22,23]. The larger blueshift appeared in GaInNAs system than in GaNAs system is due to the additional effect induced by the existent of In atoms in annealing process, such as the In-N interaction or the formation of N-In bonds due to the Ga site around N atom replaced by In atom through the point-defect assisted reorganization in the annealing process [24].…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Now that device-quality material grown by MOVPE is emerging, it is important to study the optical properties of this material to compare and contrast parameters and modeling in detail to the MBE case. [13][14][15][16][17][18] In this letter, we investigate the detailed optical characterization of high-quality strain-compensated GaInNAs single-quantumwell ͑SQW͒ material grown by MOVPE, from a growth system proven to produce high-performance laser diodes. 12 In addition to the interband transitions between quantized QW states observed by photoluminescence excitation ͑PLE͒, polarized PL properties are also reported, which is important on the one hand to verify the transition assignments and modeling approach, and on the other hand for the development of devices such as polarization-insensitive semiconductor optical amplifiers.…”
mentioning
confidence: 99%
“…2. If we assume that the variations in the peak energies of the fitted Gaussian curves are solely due to the non-uniform nitrogen concentration between the quantum wells, the maximum extent of deviations from the nominal nitrogen concentrations inside the wells are calculated using the effective masses reported in [7]. We found that these deviations are within 18% (0.0167, 0.0157, and 0.014) and 25% (0.0105, 0.0094, and 0.008) of the nominal nitrogen concentration, i.e.…”
mentioning
confidence: 99%